Clinical Outcome of ET-743 (Trabectedin; Yondelis) in High-Grade Uterine Sarcomas: Report on Five Patients and a Review of the Literature. Issue 2 (1st January 2009) - Amant, Frédéric; Coosemans, An; Renard, Vincent; Everaert, Els; Vergote, Ignace
Abstract : Abstract: The clinical impact of ET-743 (trabectedin; Yondelis) in women with leiomyosarcoma and undifferentiated uterine sarcoma in patients previously treated with chemotherapy is investigated. Current data show a clinical benefit in 2/5 patients, of which 1 had a partial remission during 9 months. Pooling the treatment outcomes with literature data, a response in 5 (38%) of 13 patients and a clinical benefit in 7 (54%) of 13 patients for all high-grade uterine sarcomas is calculated. When only uterine leiomyosarcomas are concerned, response rate is 5 (45%) of 11 patients with a clinical benefit in 7 (64%) of 11 patients. These results on the use of ET-743 in uterine sarcoma patients support the conductance of larger trials.